2011
DOI: 10.1111/j.1750-3841.2011.02173.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Characteristics and Cross‐Cultural Consumer Acceptability of Bulgogi (Korean Traditional Barbecued Beef)

Abstract: The food industry is increasingly interested in ethnic foods that satisfy sophisticated appetite of today's consumers. Korean cuisine is recently gaining popularity and perceived as "adventurous and spicy," appealing to researchers and marketers in the food industry worldwide. However, it is not easy to develop a new product based on ethnic cuisine because nonsensory factors, such as food neophobia and openness to new culture, can evoke adverse responses from the consumers. A systematic sensory approach can gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…SP-M and N-SP-M also tended to have a higher sweet taste compared to SP, though there was no significance (p>0.05) observed (Table 3). It was reported that an increase in sweetness, saltiness, and soy sauce odor/flavor was found when amounts of soy sauce and sugar levels were increased by 30% each in the study of Hong et al (2) which investigated Korean and US consumers' acceptability of bulgogi with different contents of main ingredients including sugar, soy sauce, and garlic. While the study of Hong et al (2) showed an increase of MSG taste when soy sauce and sugar levels were increased by 30% each, it was not observed in the present study.…”
Section: Sensory Characteristics and Cross-cultural Acceptability Of mentioning
confidence: 97%
See 3 more Smart Citations
“…SP-M and N-SP-M also tended to have a higher sweet taste compared to SP, though there was no significance (p>0.05) observed (Table 3). It was reported that an increase in sweetness, saltiness, and soy sauce odor/flavor was found when amounts of soy sauce and sugar levels were increased by 30% each in the study of Hong et al (2) which investigated Korean and US consumers' acceptability of bulgogi with different contents of main ingredients including sugar, soy sauce, and garlic. While the study of Hong et al (2) showed an increase of MSG taste when soy sauce and sugar levels were increased by 30% each, it was not observed in the present study.…”
Section: Sensory Characteristics and Cross-cultural Acceptability Of mentioning
confidence: 97%
“…In addition, soy protein was again added to the bulgogi formulation to investigate the effect because the effect was not revealed well in the first phase of the study. Finally, amounts of sugar and soy sauce were changed, since these ingredients were found to affect consumers' liking for bulgogi, not just Korean, but also for non-Korean consumers such as US consumers (2). Sensory characteristics of 6 RTH bulgogi: ANOVA was performed on descriptive analysis data and the result showed significant (p<0.05) differences among bulgogi samples for all sensory attributes (Table 3).…”
Section: Sensory Characteristics and Cross-cultural Acceptability Of mentioning
confidence: 99%
See 2 more Smart Citations
“…However, sensory tests focused mainly on hedonic ratings in these studies. Recently, Hong et al (12) investigated cross-cultural acceptance for bulgogi by consumers in Korea and the US using a comprehensive approach that involved a descriptive sensory analysis, hedonic ratings, and JAR ratings. That study showed that the factors affecting consumer liking in each country could be effectively identified by relating a descriptive analysis result to hedonic and JAR ratings.…”
Section: Introductionmentioning
confidence: 99%